Durum Wheat Roots Adapt to Salinity Remodeling the Cellular Content of Nitrogen Metabolites and Sucrose - Annunziata, Maria Grazia; Ciarmiello, Loredana F.; Woodrow, Pasqualina; Maximova, Eugenia; Fuggi, Amodio; Carillo, Petronia (Frontiers in Plant Science, 2017)
Plants are currently experiencing increasing salinity problems due to irrigation with brackish water. Moreover, in fields, roots can grow in soils which show spatial variation in water content and salt concentration, also because of the type of irrigation. Salinity impairs crop growth and productivity by inhibiting many physiological and metabolic processes, in particular nitrate uptake, translocation and assimilation. Salinity determines an increase of sap osmolality from about 305 mOsmol kg-1 in control roots to about 530 mOsmol kg-1 in roots under salinity. Root cells adapt to salinity by sequestering sodium in the vacuole, as a cheap osmoticum, and showing a metabolic remodelling of few nitrogen-containing metabolites and sucrose in the cytosol, both for osmotic adjustment and oxidative stress protection, thus providing plant viability even at low nitrate levels. Mainly glycine betaine and sucrose at low nitrate concentration, and glycine betaine, asparagine and proline at high nitrate levels can be assumed responsible for the osmotic adjustment of the cytosol, the assimilation of the excess of ammonium and the scavenging of ROS under salinity. High nitrate plants with half of the root system under salinity accumulate proline and glutamine in both control and salt stressed split roots, revealing that osmotic adjustment is not a regional effect in plants. The expression level and enzymatic activities of asparagine synthetase and Δ1-pyrroline-5-carboxylate synthetase, as well as other enzymatic activities of nitrogen and carbon metabolism, are analysed.